Cortisol and testosterone in association with history of sexual abuse within incarcerated adolescent youth - Miocevic, Olga (2017)
Adolescence is a challenging developmental transition in the lives of young adults, yet despite these challenges youth must normatively transition through adolescence and take on adult roles and responsibilities. Research on the topic of adolescence has addressed many of the biological, psychological, and social changes that occur during this time and this evidence converges on the notion that this normative transition can be a period of vulnerabilities or opportunities. Exposure to many forms of early adversity can exacerbate the biopsychosocial challenges of adolescence, with emerging research illustrating that child abuse and maltreatment exert particularly deleterious consequences on adolescent physiology and development. What is under-studied is whether specific forms of maltreatment in early life have immediate and long lasting effects on physiological health and wellbeing of developing youth. The present study examined cortisol and testosterone, two hormones that play important roles in adolescence and pubertal development. In addition to being acutely responsive to context, the two hormones follow a diurnal rhythm, which is highly associated with health outcomes. The present study examined effects of sexual abuse on diurnal testosterone and cortisol of incarcerated adolescent girls and boys (N=101, 49.5% female, 53% Non-White), ages 13-18 (M=16.17). The present study examined whether sexual abuse had a unique effect on cortisol and testosterone diurnal slopes for males and females. Gender was explored as a potential moderator of the relationship between sexual abuse and hormones. Race, BMI, and puberty were controlled for in examining the effects of sexual abuse on waking hormones and diurnal slope. Sexually abused youth had steeper cortisol slopes (p<.005). Girls had flatter cortisol slopes (B=.088, p<.05) and lower waking testosterone (p<.001). No significant effect of sexual abuse on testosterone was found after controlling for gender. Examining cortisol and testosterone rhythms as a function of sexual abuse can inform research and practice of the potentially adaptive response to this form of trauma in a highly vulnerable sample. Finally, information gathered from this study can open doors for improvement of intervention and prevention strategies, particularly for at-risk youth growing up in unfavorable environments